1995
DOI: 10.1007/bf00365567
|View full text |Cite
|
Sign up to set email alerts
|

Field and genetic studies testing optimal outcrossing in Agave schottii, a long-lived clonal plant

Abstract: In thisstudy we combine field experiments, designed to test the predictions of optimal outcrossing theory in Agave schottii, with molecular genetic studies, using RAPD (random amplified polymorphic DNA), polymerase chain reaction to assess the underlying genetic hypothesis of optimal outcrossing theory. Initially, 48 "females" of A. schottii were hand-pollinated with pollen collected from 1 m, 10 m, 100 m, and 2500 m distances. Each female received all four distance treatments. Additionally, a subset of the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 43 publications
3
38
0
3
Order By: Relevance
“…Our findings are in line with Trame et al (1995) who reported a negative relationship between genetic similarity and spatial distance of parent plants as well as a significant biparental inbreeding depression for Agave schottii (Agavaceae). However, to our knowledge there are as yet no studies that have tested this relationship directly using genetic differences and progeny vigour or which have clearly detected evidence of the occurrence of biparental inbreeding depression in wind-pollinated angiosperm trees.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with Trame et al (1995) who reported a negative relationship between genetic similarity and spatial distance of parent plants as well as a significant biparental inbreeding depression for Agave schottii (Agavaceae). However, to our knowledge there are as yet no studies that have tested this relationship directly using genetic differences and progeny vigour or which have clearly detected evidence of the occurrence of biparental inbreeding depression in wind-pollinated angiosperm trees.…”
Section: Discussionsupporting
confidence: 92%
“…However, several authors report that effects of biparental inbreeding are more pronounced in fitness components of the seedlings rather than in earlier life stages (e.g. Waser and Price 1994;Trame et al 1995). In accordance, a previous study on P. australis showed no significant differences in seed germination following hand outcrosses with pollen from varying distances ).…”
Section: Introductionsupporting
confidence: 68%
“…In consequence, the numerous studies on the intensity of ID in early stages of development (Waser and Price, 1993;Trame et al, 1995;Hardner et al, 1998;Melser et al, 1999) necessarily underestimate the total intensity of ID by not covering the entire life cycle. Indeed, in crosspollinated species strong ID can be expressed both early and late in their life cycle, whereas in selfing species the magnitude of ID increases along the life cycle, with the greatest values in the late stages (Husband and Schemske, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the alleles responsible for inbreeding depression and heterosis (which are unconditionally deleterious), alleles creating genetic incompatibilities become deleterious only when they interact with a foreign genetic background. In amongpopulation crosses, either heterosis or outbreeding depression, depending on the pairs of populations considered, has been observed in natural populations of plants (Waser and Price 1994;Trame et al 1995;Byers 1998;Fenster and Galloway 2000;Waser et al 2000;Pélabon et al 2005;Willi and Van Buskirk 2005) and animals (Burton 1990;Edmands 1999;Gharrett et al 1999;Aspi 2000;Andersen et al 2002;Gilk et al 2004).…”
mentioning
confidence: 99%